2020
DOI: 10.1021/acs.jmedchem.9b02022
|View full text |Cite
|
Sign up to set email alerts
|

Novel β- and γ-Amino Acid-Derived Inhibitors of Prostate-Specific Membrane Antigen

Abstract: Prostate-specific membrane antigen (PSMA) is an excellent biomarker for the early diagnosis of prostate cancer progression and metastasis. The most promising PSMA-targeted agents in the clinical phase are based on the Lys−urea−Glu motif, in which Lys and Glu are α-(L)-amino acids. In this study, we aimed to determine the effect of βand γ-amino acids in the S1 pocket on the binding affinity for PSMA. We synthesized and evaluated the βand γ-amino acid analogues with (S)-or (R)-configuration with keeping α-(L)-Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Cancers 2021, 13, x FOR PEER REVIEW 7 of 31 negative impacts on affinity towards PSMA when employing β-and γ-amino acids compared to the α-amino acid counterparts [68]. Similar negative effects were observed by Kwon et al by inverting the configuration of the α-amino acid in the binding region of the moiety [69].…”
Section: Binding Entitymentioning
confidence: 59%
See 4 more Smart Citations
“…Cancers 2021, 13, x FOR PEER REVIEW 7 of 31 negative impacts on affinity towards PSMA when employing β-and γ-amino acids compared to the α-amino acid counterparts [68]. Similar negative effects were observed by Kwon et al by inverting the configuration of the α-amino acid in the binding region of the moiety [69].…”
Section: Binding Entitymentioning
confidence: 59%
“…Thereafter, the development of the Glu-urea-Lys (EUK) entity introduced a third subgroup of urea-based inhibitors (Figure 2) [66,67]. EUK-based inhibitors have thus far been the base for the most successful PSMA-targeting LMW inhibitors, such as 18 F-DCFPyL or the FDA-approved, 68 Ga-labelled PSMA-11 for PET imaging or the theranostic variants PSMA-617 and PSMA I&T. Moreover, scientists recently explored further modifications in this PSMA-binding moiety. For example, Kim et al demonstrated the negative impacts on affinity towards PSMA when employing βand γ-amino acids compared to the α-amino acid counterparts [68].…”
Section: Linkers and Chelatorsmentioning
confidence: 99%
See 3 more Smart Citations